Information and communication technology (ICT) on economic growth in Asia: A panel data analysis - Debbra Toria Nipo; Jaratin Lily; Sidah Idris; Saizal Pinjaman; Imbarine Bujang (The Canadian Center of Science and Education, 2022)
Information and communication technology (ICT) plays an increasingly important role in driving economic growth and sustainability. Asia, being the most heterogenous region in terms of ICT development, consist of both most connected and least connected countries based on the global ICT Development Index 2017. Therefore, this study investigates the impact of ICT on economic growth for 20 Asian countries from year 2000 to 2020. Using the robust panel Fixed Effect model and Panel Feasible Generalized Least Squares method, findings revealed that fixed telephone subscriptions, mobile cellular subscriptions and Internet users are the ICT variables that have significant and positive effects on economic growth in Asia. Fixed telephone subscriptions however, emerged insignificant which could be due to its high cost and low practicality relative to other forms of ICT. Findings from this study benefit related parties such as firms and policymakers by encouraging adoption and usage of mobile phones and the Internet through provision of adequate infrastructure and affordable ICT services.